2022
DOI: 10.3390/plants11233245
|View full text |Cite
|
Sign up to set email alerts
|

Soil Treatment with Nitric Oxide-Releasing Chitosan Nanoparticles Protects the Root System and Promotes the Growth of Soybean Plants under Copper Stress

Abstract: The nanoencapsulation of nitric oxide (NO) donors is an attractive technique to protect these molecules from rapid degradation, expanding, and enabling their use in agriculture. Here, we evaluated the effect of the soil application of chitosan nanoparticles containing S-nitroso-MSA (a S-nitrosothiol) on the protection of soybeans (Glycine max cv. BRS 257) against copper (Cu) stress. Soybeans were grown in a greenhouse in soil supplemented with 164 and 244 mg kg−1 Cu and treated with a free or nanoencapsulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
(93 reference statements)
1
7
0
Order By: Relevance
“…2 ). Similar findings were reported in soybean under heavy metal [ 25 ] and maize under salt stress [ 10 ] who used encapsulated S-nitroso-mercaptosuccinic acid.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…2 ). Similar findings were reported in soybean under heavy metal [ 25 ] and maize under salt stress [ 10 ] who used encapsulated S-nitroso-mercaptosuccinic acid.…”
Section: Discussionsupporting
confidence: 85%
“…In a similar study, foliar spray of sugarcane plants with GSNONP under drought induced the antioxidative defense system [ 21 ]. In another study higher CAT and APX activity were recorded under drought stress following soil application of NO-chitosan nanoparticles [ 25 ]. Chitosan-GSNO nanoparticles enhanced several root related traits such as total length, volume, surface area, number of root tips and forks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NO-releasing nanomaterials have been extensively studied in biomedicine, their applications in agriculture are still in their infancy . Few studies have reported the use of NO-releasing nanomaterials in plants, and our research group has strongly contributed to the design and applications of NO-releasing polymeric nanoparticles in plants under different abiotic stress conditions. This is a hot topic that has still not been fully explored and deserves further investigations. The following sections detail the important and recent progress in the use of NO donors allied with nanomaterials in different biomedical and agricultural applications.…”
Section: Combination Of No Donors With Nanomaterials: Challenges and ...mentioning
confidence: 99%
“…Both nanoencapsulated and free S -nitroso-MSA application improved plant growth and maintained photosynthetic activity in Cu-stressed plants. Interestingly, only the nanoencapsulated S -nitroso-MSA increased NO bioavailability in the roots, resulting in enhanced antioxidant activity, reduced oxidative damage, and improved mitigation of root nutritional imbalance caused by Cu stress . These findings highlight the effectiveness of nanoencapsulation in delivering NO and providing enhanced protection to soybean plants under Cu stress.…”
Section: No-releasing Nanomaterials In Agricultural Applicationsmentioning
confidence: 99%